Studi Onomastika Biblikal dalam Sejarah Linguistik Penulisan Teks Perjanjian Baru - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2019)
This article examines the proper names in the New Testamment including the study of those etymologies and terminologies. The study in this article is related to the linguistic history in Miditeranian sea surrounding areasthat have become the writting locus of New Testamment original text. The discussion has been conducted with linguistic and historical approaches in both biblical and geographical context. From the research that has been undergone, there is an important fact that there was a language development history in the area arround Miditeranian sea. The usage of Greek language as the language of New Testament is strongly connected to the history of the Greece in that area. The names in New Testamment show that there were various languages that had been existed and used in NT written locus. NT reports that there are various names from several different languages related to the history of that area such as Hebrew, Aramic, Latin and Greek.